Eksistensi Permainan Jujungke pada Etnis Muna di Desa Lakapodo Kecamatan Watopute Kabupaten Muna - Irma Magara; Hilwa Salsabila; Rahmat Sewa Suraya (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2024)
The Jujungke game is a traditional leg bending game accompanied by the Jujungke song with 3-5 players. The aims of this research are (1) to describe the form of the Jujungke folk game (2) to find out the values contained in the Jujungke game, (3) To analyze the reasons why the Jujungke game still survives today in the community in Lakapodo Village, Watopute District, Muna Regency. The method used is a qualitative research method. The data in this research was obtained through participant observation and in-depth interviews supported by documentation and recording/video. Informants were determined using the purposive method. The informants in this research were the community, elementary school teachers and children in Lakapodo Village. The data analysis technique in this research consists of three stages, namely data reduction, data presentation, and conclusions. The results of this research show that (1) the values contained in the traditional Jujungke game are the value of joy, the value of togetherness, cultural value and social value. The Jujungke game is a game that is preserved by the people of Lakapodo Village, Watopute District, Muna Regency to this day. (2) The driving factors for traditional Jujungke games to survive to this day are the role of parents who encourage and motivate their children to play economical and practical traditional Jujungke games, the cultural preservation of traditional Jujungke games, the transformation from the older generation to the younger generation, and efforts and cooperation of residents in preserving the traditional Jujungke game.